Patient satisfaction across surgical units in tertiary care hospitals - R. Padma Hepsiba , Dr. Tapti Bhattacharjee (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Patient satisfaction is the most primary thing during surgeries in tertiary care hospitals. Based on the expectations of the patients, evolutions of the hospitals take place. In every health care institution, patient-level satisfaction assessment has become more important in terms of enhancing quality as well as maintaining the sustainability of the hospitals. In this article, we will discuss patient satisfaction in tertiary care hospitals across surgical units. The surgical unit is one of the important parts of the hospitals where patients receive special treatment and medications and recover through the surgical procedure. Patents are sent to the surgical units in critical cases where they need quality of care and protection. Satisfaction among the patients in the surgical units is most important for the recovery of the patients.